WORK STUDY IMPROVEMENT FOR CUERVO (ANALOG) PRODUCT IN AN ELECTRONIC INDUSTRY - A. P., Puvanasvaran; S.T.Kerk, Robert; A. R. , Ismail (2010)
Many industries are applied a work study techniques in order to gives benefits for investigating human work and leading to further improving of work productivity. This paper determines the improvement of the work study technique in ensuring the reduction of the processing time for the Cuervo (analog) product. All the information related to work study practices and the improvement in the time study aspect were compiled from related journals, books and internet sources. This study was conducted in an electronic industry in Malaysia. A time study is used in order to define the steps in a production procedure and the time consumed by the worker for the increasing efficiency or productivity of workers in full time and motion study.